(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Penaeus; White spot syndrome (WSSV); virus; tiger shrimp; PCR Bangladesh j. genet. biotechnol. 7(1&2): 37-42 2006 (June & December)